Self-monitoring of health - user viewpoints on gathering data using consumer health technologies during leisure time - Nora Weinberger; Martina F. Baumann; Maria Maia (Frontiers in Digital Health)
IntroductionConsumer Health Technologies (CHTs), including wearables and brain-activity monitoring devices, are increasingly integrated into everyday life, extending beyond clinical settings into leisure activities. Yet, their ethical and social implications, especially in unregulated, non-clinical contexts, remain underexplored.MethodsThis qualitative study examines how individuals perceive and engage with CHTs by combining guided interviews and pre-interview questionnaires. It focuses on attitudes toward health data collection, data sharing, privacy concerns, and the use of EEG-supported devices.ResultsFindings reveal a complex landscape of trust and concern. While participants generally favored sharing data with research institutions over corporations or insurers, they were skeptical about broad consent models. Some acknowledged potential health benefits of CHTs and EEG-supported technologies, but also expressed concerns about data security, behavioral pressure, and the normalization of self-optimization.DiscussionThe results underscore the need to center user perspectives in the development of CHTs, to promote transparent and context-sensitive privacy policies, and to anticipate ethical implications. In particular, the article argues for ethical frameworks to guide the use of EEG-supported technologies in everyday settings, ensuring alignment with societal values and equitable access to digital health benefits.